PSYCHOLOGICAL CHALLENGES IN LEARNING ENGLISH AS A FOREIGN LANGUAGE (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This article provides an in-depth analysis of psychological problems faced by learners while studying English as a foreign language. In the era of globalization, knowing English has become an essential skill for students. However, many learners encounter several psychological obstacles, such as lack of motivation, language anxiety, low self-confidence, and poor emotional readiness. Additionally, the learning environment, student-teacher relationships, and classroom emotional atmosphere also significantly impact the acquisition of the language. The article also discusses modern approaches to overcoming these difficulties, including student-centered education, the development of emotional intelligence, and strategies aimed at improving psychological readiness.